Community Economic Empowerment Strategy Through PRO UKM Lazis MUM Padang City - Fitri, Nadia Yulia; Fadri, Zainal (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2022)
The purpose of this discussion is to find out the strategies, outputs and supporting and inhibiting factors of LAZIS Mitra Ummat Madani in Padang City in empowering the community's economy through PRO UKM. The type of research that the author uses is a type of field research (Field Research), to obtain data from the problems studied. Data collection techniques that the authors use is through interviews and documentation. Data management was carried out in a qualitative descriptive manner, then described and classified aspects of certain problems and explained through effective sentences. Based on the research that has been done, the researchers get the results that 1) the strategy carried out by LAZIS Mitra Ummat Madani Padang City in empowering the community's economy through PRO UKM is to find mustahik who really need business capital assistance through PRO UKM to the field, in addition to PRO UKM assistance distributed to mustahik in the form of goods not in the form of cash. 2) the output of the strategy carried out by LAZIS Mitra Ummat Madani in Padang City in empowering the community's economy through PRO UKM, not only empowering in terms of economy, but in terms of religion and psychology, such as in terms of religion, mustahik have started to give alms, while in terms of family psychology, it is more harmonious and children are not neglected. 3) supporting and inhibiting factors for LAZIS Mitra Ummat Madani in Padang City in empowering the community's economy through PRO UKM, and supporting factors.